The effect of environmental conditions in the duration of daily grazing itineraties of small ruminants in Northeast Portugal - Castro, Marina (2012)
The production of small ruminants (sheep and goats) in Northeast Portugal is an extensive activity, mainly based on exploitation of spontaneous resources. The shepherds direct their flocks on daily grazing itineraries over different types of resources. These itineraries vary throughout the year, in both duration and locations visited. The aim of this study is to analyse the variation of the grazing circuits in relation to the environmental conditions. The time spent by flocks on each itinerary varied from 381 to 746 minutes for goat flocks, and from 300 to 921 minutes for sheep flocks, depending on the duration of daylight. Nevertheless, other environmental conditions have an important role on the pattern of grazing circuits, such as mid-day temperature and abundance of resources.